2021
DOI: 10.3906/yer-2105-28
|View full text |Cite
|
Sign up to set email alerts
|

Surface heat flow in Western Anatolia (Turkey) and implications to the thermal structure of the Gediz Graben

Abstract: Knowledge of heat flow density on the Earth's surface and subsurface temperature distribution is essential for the interpretation of several processes in the crust such as for the evaluation of the geothermal potential of a region. With this study, we investigate the conductive heat flow distribution in western Anatolia to understand the thermal state and its relationship to regional tectonics in the region. The new heat flow data are collected and combined with previously published data to obtain the new heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For comparison, a tomographic image of the surface group wave velocity obtained from this study for 2 s period (Figure 8A) is shown together with Bouger gravity anomaly (Figure 8B), heat flow (Figure 8C), and magnetic (Figure 8D) results reported by Gonenc et al, 2012, Pamukcu et al, 2019, Pazvantoglu et al, 2021Teknik et al, 2023. We interpret the low velocity zones in offshore areas (e.g., IB, CB) as sedimentary sequences overlying a Miocene basement. The size of the IB low velocity zone is 50 × 20 km (Figure 8A).…”
Section: Figurementioning
confidence: 61%
See 2 more Smart Citations
“…For comparison, a tomographic image of the surface group wave velocity obtained from this study for 2 s period (Figure 8A) is shown together with Bouger gravity anomaly (Figure 8B), heat flow (Figure 8C), and magnetic (Figure 8D) results reported by Gonenc et al, 2012, Pamukcu et al, 2019, Pazvantoglu et al, 2021Teknik et al, 2023. We interpret the low velocity zones in offshore areas (e.g., IB, CB) as sedimentary sequences overlying a Miocene basement. The size of the IB low velocity zone is 50 × 20 km (Figure 8A).…”
Section: Figurementioning
confidence: 61%
“…The Aegean region of Türkiye is affected by frequent seismic activity, mostly of low magnitude (Coban and Sayil, 2019;Ozturk, 2019;Ankaya Pamukcu et al, 2021), and shows high heat flow (Pazvantoglu et al, 2021) and geothermal activity (Ozer and Polat, 2017a). Only few moderate earthquakes have been recorded in the study area (e.g., Mw6.2 Lesvos-Izmir earthquake on 12 June 2017, Mw6.5 Bodrum-Kos earthquake on 21 July 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation